Histomorphometry and Protein Expression From the Ovary and Uterine Horns of Wistar Strain Albino Rats Treated with Methanol Leave Extract of Parquetina Nigrescens - Akinjiola, Akinwale Modupe; Ajala, Oluwatoyin Oluwasola; Aina, Oluwasanmi Olayinka; Oyebanji, Victor Olawale; Olukunle, Johnny Olufemi (Drug Research, 2018)
Background The effects of methanol extract of Parquetina nigrescens were studied on histomorphometry and protein expression (SDS-PAGE) from the ovaries and uteri of wistar rats.Methods 30 sexually matured rats were used for the study with 10 each in the control and treatment 100 mgkg−1 and 400 mgkg−1 groups. The extract was orally administered for 14 days. Histological sections of tissues collected presented no abnormalities.Results An increase in the number of developing and matured follicles were observed during the study in the treated groups compared to the control in the follicular and the luteal phases. The corpora lutea in the treated groups were fewer in number to that of the control in the follicular phase and in the luteal phase. Sections of the uterine horns showed significant narrowing in the lumen diameter and increases in epithelial height with increased laydown of the lamina propria in the treated groups. The expression of protein bands fractionated during the study, confirm the presence of proteins expressed repeatedly from the ovary and uterine horns in the follicular and luteal phases at the 70 kDa and 63 kDa regions.Conclusions The study concluded that the methanol extract of the plant increased folliculogenesis on the ovary, secretory activity in the nuclei of the epithelium and the fibroplasia of the lamina propria while narrowing the lumen of the uterine horns which are similar to the effects of oestrogen or oestrogen-like substances on these reproductive organs and may have an effect on the abundance of protein expressed in the follicular phase.
Keywords: ovaries; uterine horn; proteome; parquetina nigrescens